Diploid Male Gametes Circumvent Hybrid Sterility Between Asian and African Rice Species - Kuniyoshi, Daichi; Masuda, Itaru; Kanaoka, Yoshitaka; Shimazaki-Kishi, Yuki; Okamoto, Yoshihiro; Yasui, Hideshi; Yamamoto, Toshio; Nagaki, Kiyotaka; Hoshino, Yoichiro; Koide, Yohei; Takamure, Itsuro; Kishima, Yuji (Frontiers in Plant Science, 2020)
In F1 hybrids of Oryza sativa (Asian rice) and O. glaberrima (African rice), heterozygosity leads to a complete gamete abortion because of allelic conflict at each of the 13 hybrid sterility (HS) loci. We systematically produced 19 plants from the F1 hybrids of both the rice species by the anther culture (AC) method. Five of the 19 interspecific hybrid plants were fertile and able to produce seeds. Unlike ordinal doubled haploid plants resulting from AC, these regenerated plants showed various ploidy levels (diploid to pentaploid) and different zygosities (completely homozygous, completely heterozygous, and a combination). These properties were attributable to meiotic anomalies in the interspecific hybrid F1 plants. Examination of the genetic structures of the regenerated plants suggested meiotic non-reduction took place in the interspecific hybrid F1 plants. The centromeric regions in the regenerated plants revealed that the abnormal first and/or second divisions of meiosis, namely the first division restitution (FDR) and/or second division restitution (SDR), had occurred in the interspecific hybrid. Immunohistochemical observations also verified these phenomena. FDR and SDR occurrences at meiosis might strongly lead to the formation of diploid microspores. The results demonstrated that meiotic anomalies functioned as a reproductive barrier occurred before the HS genes acted in gamete of the interspecific hybrid. Although such meiotic anomalies are detrimental to pollen development, the early rescue of microspores carrying the diploid gamete resulted in the fertile regenerated plants. The five fertile plants carrying tetraploid genomes with heterozygous alleles of the HS loci produced fertile diploid pollens, implying that the diploid gametes circumvented the allelic conflicts at the HS loci. We also proposed how diploid male gametes avoid HS with the killer-protector model.